Management of Complex Fistula in Ana with Fistulotomy and Stage Procedure (Journal of Dhaka Medical College, 2018)
Background: Complex fistula in ano is a troublesome disease and is difficult to treat. Complex fistula in ano occurs in various forms like multiple external and/or internal openings, internal opening above the dentate line, external opening far away from anal verge, anterior tract etc. They are almost invariably recurrent and frequently associated with other systemic diseases like tuberculosis, inflammatory bowel disease, malignancy etc.A complex fistula in ano has various modalities of treatments like application of setons, fistulotomy or fistulectomy, endorectal advancement flap, anocutaneous advancement flap, fistula plug, fibrin glue, electrocauterization of tract/laser and ligation of intersphincteric fistula tract (LIFT).Objective: The purpose of the study is to evaluate the outcome of complex fistula in ano by fistulotomy and staged procedure.Methods: The study was held in Dhaka medical college Hospital and various private hospitals located in Dhaka and Brahmonbaria within duration of 8 years (from January, 2011 to January, 2018). Among 256 patients (221 male, 35 female) with median age 48 years (30 to 72 years) with the diagnosis of complex fistula in ano, 135 underwent fistulotomy with application of Seton with stage procedure. 121 patients underwent single stage fistulotomy. 158 patients had history of previous operations. After stage procedure, regular follow up was done every week until wound healing occurred.Result: Among 256 patients 121 patients (47%) underwent single stage, 133 (52%) patients underwent two stage and 2 patients underwent three stage procedure during the trial period. Majority of the patients had minor incontinence; that is flatus and/or loose stool incontinence. But they only persisted for an average of 10 to 16 days and subsided spontaneously. None of the patient had any major (solid stool) incontinence. 4 patients (2%) had recurrence of fistula on an average of 3-6 months after complete healing. Recurrence occurred in the form of abscess, automatically burst internally, recurrent fistula.2 patients developed bleeding after single stage procedure and was managed by cauterization.Conclusion: With adequate postoperative care and regular follow up, application of Seton with ‘staged procedure’ in cases of complex fistula in ano is very effective and has very minimal complications. Chance of major incontinence and recurrence is also less.J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 83-87